Internet browsing and Web 2.0 Competencies as Correlate of Effective Management of Institutional Repository by Librarians in Federal Universities in South-South, Nigeria - Robinson , Janet Nnenta; Ukaegbu, Bernadette C. N. (yocto brain, 2024)
This study was carried out to investigate Internet browsing and Web 2.0 competencies as correlate of effective management of institutional repository by Librarians in federal universities in South-South, Nigeria. Utilizing a correlational design, the study answered three questions and tested three hypotheses. The cohort of 242 Librarians from seven federal universities—115 academic and 127 non-academic—constituted the study's population. A stratified total census sampling approach was deployed to include all 242 librarians. Data gathering utilized two questionnaires: the